Modeling the asymmetric in conditional variance - Agboluaje, Ayodele Abraham; Ismail, Suzilah; Yip, Chee Yin (Science Alert, 2016)
The purpose of this study is to model the asymmetric in conditional variance of Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH) with Combine White Noise (CWN) model to obtain suitable results. Combine white noise has the minimum information criteria and high log likelihood when compare with EGARCH estimation.The determinant of the residual covariance matrixvalue indicates that CWN estimation is efficient. Combine white noise has minimum information criteria and high log likelihood value that signify suitable estimation. Combine white noise has a minimum forecast errors which indicates forecast accuracy.Combine white noise estimation results have proved more efficient when compared with EGARCH model estimation